The Impact of Learning Loss due to Family Income Factors on Students' Achievement during the COVID-19 Pandemic - Falinda Oktariani; Richa Fionasari; Triana Ramdha (Edunesia: Jurnal Ilmiah Pendidikan, 2022)
The purpose of this study is to examine online learning during the pandemic period from the learner's economic standpoint. Seeing how far family income influences student learning achievement from the perspective of mastering English. The data is derived from English academic achievement and a questionnaire focusing on students' economic situations, and it is analyzed using the SPSS version 23 application. After being determined to be homogeneous and normally distributed, the data was collected and analyzed to test the hypothesis using R Square and ANOVA techniques. The results show that family economic factors influence Riau University students' English proficiency as much as 69.7 % in 2021 during the COVID-19 pandemic which may result in learning loss for the students